Optical burst switching for service differentiation in the next-generation optical Internet. - Yoo, Myungsik (IEEE Communications magazine)
In an effort to eliminate the electronic bottleneck, new optical switches/routers (hardware) are being built for the next-generation optical Internet where IP runs over an all-optical WDM layer. However, important issues yet to be addressed in terms of protocols (software) are how to develop a new paradigm that does not require any buffer at the WDM layer, as in circuit switching, and elimination of any layers between which exist mainly due to historical reasons. At the same time, such a paradigm should also efficiently support bursty traffic with high resource utilization as in packet switching. This article surveys design issues related to a new switching paradigm called optical burst switching, which achieves a balance between circuit and packet switching while avoiding their shortcomings. We describe how OBS can be applied to the next-generation optical Internet, and in particular how offset times and delayed reservation can help avoid the use of buffer, and support quality of service at the WDM layer